Eco-enzyme Making Assistance for Family Welfare Guidance Women - Siti Patonah; Lussana Rossita Dewi; Ummi Kaltsum (Universitas Lambung Mangkurat, 2024)
The lack of understanding and skills of Family Welfare Guidance women in Bawen Village in making eco-enzymes in processing organic waste impacts the suboptimal processing of household-based waste. This community service program aims to provide counseling, education, and practice in making eco-enzymes. The methods used in this activity are socialization and counseling, practical training in making, harvesting, and application. The activity lasted for five months, starting from January to May 2023. The results of this activity are twofold: participants' increased understanding of eco-enzymes, participants' ability to make eco-enzymes, participants' ability to harvest eco-enzymes, and participants' ability to use eco-enzymes for various kitchen and plant fertilization purposes. All participants were able to make, harvest, and use eco-enzymes. The increase in participants' understanding is evident.